Mediastinal emphysema following fracture of the orbital floor - Abdelrahman, Husham (Oxford University Press, 2014)
Pneumomediastinum (PM) is mainly an atypical finding among traumatic neck or thoracic injury patients. Moreover, PM secondary to isolated orbital floor fracture remains a rare event which is infrequently associated with severe complications such as mediastinitis, airway obstruction and pneumothorax. Herein, we report an atypical case of mediastinal emphysema consequent to orbital floor fracture along with review of the literature.